2009
DOI: 10.1186/1471-2180-9-7
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the meningococcal DNA glycosylase Fpg involved in base excision repair

Abstract: Background: Neisseria meningitidis, the causative agent of meningococcal disease, is exposed to high levels of reactive oxygen species inside its exclusive human host. The DNA glycosylase Fpg of the base excision repair pathway (BER) is a central player in the correction of oxidative DNA damage. This study aimed at characterizing the meningococcal Fpg and its role in DNA repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 45 publications
1
9
0
Order By: Relevance
“…While we found that MutM has glycosylase/lyase activity against 8-oxoG·C (Fig. 2 E ), Nth failed to remove this lesion (Table 1), which is consistent with previous results in E. coli and N. meningitidis (Morland et al, 2002, Tibballs et al, 2009). MutM excised 8-oxoG·C with the highest rate constant observed ( k cl , 0.1 ± 0.006 s −1 ) for this enzyme with any substrate tested.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…While we found that MutM has glycosylase/lyase activity against 8-oxoG·C (Fig. 2 E ), Nth failed to remove this lesion (Table 1), which is consistent with previous results in E. coli and N. meningitidis (Morland et al, 2002, Tibballs et al, 2009). MutM excised 8-oxoG·C with the highest rate constant observed ( k cl , 0.1 ± 0.006 s −1 ) for this enzyme with any substrate tested.…”
Section: Resultssupporting
confidence: 92%
“…E. coli MutM was initially named Fpg because formamidopyrimidine (FAPY) was its first characterised substrate (Chetsanga & Lindahl, 1979, Boiteux et al , 1989). However, as the E. coli and meningococcal enzymes both recognise other DNA lesions including 8-oxoG (Tibballs et al, 2009, Morland et al , 2002), we refer to this enzyme as MutM (Nghiem et al , 1988). Nothing is known about the activity of the putative meningococcal Nth (encoded by NMB0533), which shares 72% amino acid identity with the E. coli enzyme that recognises a broad range of oxidised pyrimidines (Dizdaroglu et al , 1993).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is especially true for the pathogenic Neisseria strains, where mutators are frequently isolated from epidemic-associated, invasive strains of N. meningitidis compared to related strains that colonize the nasopharynx and rarely cause invasive disease (38). Disrupted genes in N. meningitidis that produce a mutator phenotype include mutS and mutL as well as the fpg and mutY glycosylases of base excision repair and 8-oxo-guanine repair pathways (6,37,38,53). The role of mutators in the natural history of Gc is less well understood, but we presume that mutator clinical isolates of Gc do exist and will be found to lack active MutS or MutL.…”
Section: Discussionmentioning
confidence: 99%
“…The DNA substrates used in the assay are listed in Table 2 . Purified DNA glycosylase Fpg [ 56 ] and bovine serum albumin (BSA) were used as positive and negative controls, respectively. Each experiment was repeated at least three times.…”
Section: Methodsmentioning
confidence: 99%